Gambaran Kecukupan Gizi pada Kehamilan Remaja di Kota Salatiga - Brigitte Sarah Renyoet; Oktavia Corry; Rifatolistia Tampubolon (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: Nutritional adequacy is one of the factors that affect the health of pregnant women and fetuses. Objective to describe the nutritional adequacy of adolescent pregnant women in Salatiga City.Methods: this study uses a mix method. The study population was all teenage pregnant women in Salatiga City. The sample is all pregnant women aged 12-16 years through total sampling technique. The instruments used were food records 2x24 hours and the SQ-FFQ form last one month for quantitative research, pens, recording tools and qualitative research log books. Quantitative data were analyzed using NutriSurvey 2007 software, qualitative data were analyzed through coding.Result: The level of macronutrient adequacy of adolescent pregnant women in Salatiga City mostly has a deficit of weight and more, namely carbohydrates (57.14%) and fat (85.71%). Most of the micronutrient adequacy levels are deficits, namely potassium (85.71%), calcium (100%), zinc (100%), iron (85.71%), folate (85.71%), vitamin B1 (100%) and vitamin E (57.14%).Conclusion: Research on the level of macronutrients adequacy of adolescent pregnant women in Salatiga City is mostly in the category of heavy and overweight deficits, namely carbohydrates and fats above 50%. The level of micronutrients adequacy in most of the deficit categories, namely potassium, calcium, zinc, iron, folate, vitamin B1 and vitamin E is above 50%. This is influenced by the imbalance of food intake consumed during pregnancy. This also results in weight gain of pregnant women not being ideal for weight gain during pregnancy, even though they have good nutritional status.